Investigating young ESL learners' comprehension of stories situated in native and non-native cultures / Sawittri Shotiwuth a/p Charun - Charun, Sawittri Shotiwuth (2012)
Children’s literature has long been regarded as appropriate and engaging materials for teaching language to young learners. Teachers of English as a second language (ESL) have found narrative texts to be effective in building language and comprehension skills. A massive volume of children’s literature, however, are produced for the native speakers in mind, thus bearing cultural references and settings that may be unfamiliar to non-native speakers. Viewed from the Schema Theory perspective – which holds that comprehension of texts is made possible through existing mental frameworks – the lack of familiarity with the culture upon which a story is situated may result in comprehension being more difficult to achieve. This is especially so when young readers with little engagement with non-native cultures read culture-laden narrative texts. In response to this issue, this study explores the extent to which culturally-acquired prior knowledge affects young ESL learners’ comprehension of narrative texts situated in native and non-native cultures. 21 Year 3 pupils from a Tamil vernacular primary school in Sungai Buloh, Selangor, Malaysia read two narrative texts situated in non-native cultures (Roman-Catholic Filipino and Great Plains Indians) and one narrative text situated in native culture (Malaysian Hindu Indian). Participants’ level of comprehension for each text was measured through written comprehension tests and verbal story retelling tasks.